Whether the Directed Technical Change Promotes the Improvement of the Energy Structure in China - Hou, Guisheng; Song, Hongyu (Frontiers in Environmental Science, 2022)
Optimizing energy structure is necessary to achieve full decarbonization. In this study, we introduced thermal power, clean energy, and traditional fossil energy as three different input factors into the translog production function. We considered three improvement paths of the energy structure, including replacing fossil energy with electricity and using thermal power to substitute for clean energy and then analyzed whether the directed technological change promotes the optimization of the energy structure in China. The results show that there is a substitution relationship between thermal power and clean energy during the internal transition process, and the biased technical change is thermal power-using, which suggests that technological change is not conducive to the improvement of electricity structure from thermal power to clean energy. In external transition, the biased technical change is fossil energy-using instead of thermal power-using or clean power-using, and there is a substitution relationship among three factors, which shows that technical change goes against the improvement of energy structure from fossil energy to electricity. We propose that the Chinese governments adopt energy price or carbon tax measures to adjust the directed technical change and thus optimize the energy structure. In addition, according to the results from China, different countries can improve the energy structure based on their characteristic production mode.